In vitro and in vivo investigations on anti-influenza effect of adamantyl (alkyl, cycloalkyl) derivatives of aminopropanol-2 - Voloshchuk, O.M.; Korotkiy, Y.V.; Rybalko, S.L.; Starosila, D.B.; Shirobokov, V.P. (Вiopolymers and Cell, 2017)
Aim. To establish anti-influenza activities for 8 compounds of adamantyl (alkyl, cycloalkyl) de-rivatives of aminopropanol-2 in vitro and in vivo investigations. Methods. The antiviral action of compounds was determined in vitro by reduction of infectious titer of the influenza virus in the Madin-Darby Canine Kidney (MDCK) cell culture and in vivo on the model of influenza pneu-monia in mice. Results. Three of eight studied compounds inhibit the reproduction of the influ-enza virus strain A/FM/1/47(H1N1) by more than 2 lg ID50 in the concentration range from < 0.39 µg/ml (the compounds 30 and 33) to 1.56 µg/ml (the compound 5), their chemotherapeutic indices are 256 and 16, respectively. The experiments in vivo showed that in prophylactic scheme the efficiency index (EI) of the compounds 5 and 30 is 60 %; in therapeutic scheme EI of the compounds 5 and 33 is 100 % that is two times higher, than for rimantadine. Conclusions. High chemotherapeutic indices of the compounds 30, 33 and their ability to suppress the influenza virus reproduction in the MDCK cell culture by more than 2 lg ID50 indicate the anti-influenza activity of these compounds. It has been also confirmed by in vivo experiment.